A comprehensive review on lactoferrin: a natural multifunctional glycoprotein. Issue 23 (16th November 2022) - Shini, V. S.; Udayarajan, Chinthu Tharayil; Nisha, P.
Abstract : Health benifts and appplication of lactoferrin. Abstract : Lactoferrin (Lf) is a natural iron-binding globular glycoprotein, present mainly in milk. It maintains human health through its multifunctional activities, including immunomodulation, iron metabolism, and antioxidant and prebiotic efficacy. It also shows anti-microbial, anti-fungal, and anti-viral activities against a broad spectrum of viruses, including SARS-CoV-2 that causes COVID-19. In addition, several investigations established that Lf is involved in bone metabolism, neural development, and metabolic disorders. In this review, we summarize the in vitro and in vivo studies on the health benefits of Lf and its bioavailability. Furthermore, we briefly describe the production, industrial applications and future prospects of Lf.